Application of multivariate analysis to identify relationships among useful agronomic characters of cowpea and differentiation of cultivars for vegetable and grain uses - M. O. Burlyaeva; M. V. Gurkina; E. V. Miroshnichenko (Труды по прикладной ботанике, генетике и селекции)
Background. Сowpea (Vigna unguiculata (L.) Walp.) is a thermophilic crop; in most countries it is grown for grain and vegetable uses. Positive results of open-field cowpea production in the southern regions of Russia and the possibility of its cultivation on infertile soils in hot and dry climate imply the need to develop new cultivars suitable for wider introduction into Russian agriculture. It is of paramount importance for cowpea breeders to know the patterns of variability in the relationships among agronomic traits and their characteristics in cultivars grown for different uses (grain and vegetable). Besides, acceleration of the breeding process to a large extent depends on the knowledge of the traits that make it possible to differentiate the source material according to its intended purpose.Materials and methods. For three years, 315 cowpea accessions of various origin from the VIR collection were studied in Astrakhan Province, Russia. Eight useful agronomic characters were examined. The variability and relationships of these characters were assessed in cultivars grown for grain and vegetable purposes using multivariate statistical analyses.Results and discussion. The characters that differentiate grain and vegetable cowpea accessions were identified: the type of seed coat surface, the presence of fiber in ventral and dorsal pod sutures and a sclerenchyma layer in pods valves, and pod length. Discriminant functions were calculated for identification and classification of accessions according to their grain and forage uses. The character (presence of depressions or longitudinal striae on the seed coat surface) diagnosing vegetable cowpea cultivars was pinpointed. Characters associated with high seed yield were identified. For grain cultivars such character is the weight of 1000 seeds, while for vegetable cultivars it is a large-seeded and long-fruit pod.